Status and Future Directions of Therapeutics and Prognosis of Cardiac Amyloidosis - Zhang W; Ding J; Wang W; Wang D; Pan Y; Xu D (Dove Medical Press, 2023)
Wenbing Zhang,1 Jian Ding,2 Wenhai Wang,1 Duo Wang,3 Yinping Pan,4 Dexin Xu5 1Department of Cardiology, Jilin Province FAW General Hospital, Changchun, 130000, People's Republic of China; 2Department of Electrodiagnosis, Jilin Province FAW General Hospital, Changchun, 130000, People's Republic of China; 3Department of Geriatrics, Jilin Province FAW General Hospital, Changchun, 130000, People's Republic of China; 4Department of Pediatrics, Jilin Province FAW General Hospital, Changchun, 130000, People's Republic of China; 5Department of Orthopedics, Jilin Province FAW General Hospital, Changchun, 130000, People's Republic of ChinaCorrespondence: Dexin Xu, Department of Orthopedics, Jilin Province FAW General Hospital, Changchun, 130000, People's Republic of China, Email bonewax@sina.comAbstract: Accumulation of aberrant proteins in the heart causes cardiac amyloidosis, an uncommon and complicated illness. It can be classified into two main types: light chain (AL) and transthyretin (ATTR). The diagnosis of cardiac amyloidosis is challenging due to its non-specific clinical presentation and lack of definitive diagnostic tests. Diagnostic accuracy has increased with the advent of modern imaging methods, including cardiac magnetic resonance imaging (MRI) and positron emission tomography (PET) scans. Depending on the severity of cardiac amyloidosis, a number of treatments may be attempted and specified according to the subtype of amyloidosis and the presence of complications. However, there are still significant challenges in treating this condition due to its complexity and lack of effective treatments. The prognosis for patients with cardiac amyloidosis is poor. Despite recent advances in diagnosis and treatment, there is still a need for more effective treatments to improve outcomes for patients with this condition. Therefore, we aim to review the current and future therapeutics reported in the literature and among ongoing clinical trials recruiting patients with CA.Keywords: cardiac amyloidosis, ATTR CA, transthyretin amyloidosis, AL CA, light-chain amyloidosis, management, treatment, stem cell transplantation, chemotherapy, immunomodulatory agents